Konsturuksi Model Supervisi Pendidikan Islam Berbasis Srah Az-Zumar untuk Mengaklerasi Mutu - AHMAD RIZKY FIRDAUS; AHMAD NOR KASTALANI; AHMAD MAULANA; BIDIN (AL-IBNOR, 2026)
Educational supervision represents a core pillar within educational administration, profoundly impacting the advancement of instructional delivery. Within an Islamic framework, this oversight transcends mere technical pedagogical enhancement, heavily emphasizing the cultivation of ethics and internal spiritual growth. This inquiry explores the structural philosophy of supervision from an Islamic viewpoint, seeking to align the profound insights embedded in Surah Az-Zumar with innovative conceptual designs for religious-based school supervision. Executed through a qualitative paradigm using a comprehensive desk research design, this analysis synthesizes diverse academic texts, theoretical books, and classic as well as modern exegesis. The structural reading of Surah Az-Zumar verse 9 reveals imperative constructs regarding intellectual appreciation, spiritual awakening, interior examination, and human development. These points can be seamlessly incorporated into Islamic school oversight via specialized professional mentorship, analytical reflection, and deep spiritual orientation. Consequently, an Islamic supervisory paradigm rooted in these celestial principles is forecasted to radically maximize instructional efficacy and foster robust teacher professionalism across Islamic educational environments.